Vitamin D Insufficiency in Patients Admitted to a Tertiary Care Hospitals Due to Polycystic Ovary Syndrome - Bushra Bashir, Zubaida Khanum Wazir, Noreen Tahir, Shermeen Kousar (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: The purpose of this research was to study vitamin D deficiency in women with polycystic ovary syndrome. Study Design: Cross-sectional study Place and Duration: Department of Gyne & Obs King Abdullah Teaching Hospital Mansehra and Gulnawaz teaching Hospital Bannu during from August 2022 to March 2023. Materials & Methods: In this research, 176 women with polycystic ovarian syndrome between the ages of 20 and 40 participated. Patients’ data including age, body mass index, illness duration, parity and residency were recorded once they gave their permission. Vitamin D insufficiency was defined as a serum 25-hydroxyvitamin D level <20 ng/ml. SPSS 22.0 was used to analyze the data. Results: In our study majority of the patients 70 (39.8%) were aged between 26-30 years, followed by 31-35 years 50 (28.4%) patients. Mean BMI of the patients was 29.23±7.55 kg/m2. We found that 120 (68.2%) patients had vitamin D deficiency. Conclusion: For individuals diagnosed with polycystic ovarian syndrome, the rate of vitamin D insufficiency was significantly greater than what was anticipated, as indicated by the outcomes of this research. Keywords: Polycystiv Ovarian Syndrome, Vitamin D Deficiency, Tertiary Care